2012
DOI: 10.4318/tjg.2012.0330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics on methionine cholinedeficient diet-induced steatohepatitis in rats

Abstract: Amaç: ‹ntestinal bakteriler, hepatik insülin direnci ve non-alkolik ya¤l› karaci¤er hastal›¤›nda patojenik rol oynayan endojen sinyalleri indük-lerler. Probiyotikler barsak floras›n› düzenleyerek karaci¤er-barsak ekseninde etki gösterebilirler. Bu çal›flmada s›çan modellerinde metiyonin ve kolinden fakir diyet ile oluflturulan non-alkolik steatohepatitte iki probiyotik kar›fl›m›n›n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Similar results were obtained by Wang et al who reported that the probiotic mixture, kefir, reduced ovalbumin induced apoptosis in mouse heart tissues by limiting levels of the pro-apoptotic proteins Bax and Bad, cytochrome c and caspase-3 [56]. Administration of probiotic mixtures also depressed expression of apoptosis linked proteins such as pro-apoptotic Bax, caspase-3 and -8, and anti-apoptotic Bcl-2 in the livers of rats fed a methionine choline-deficient diet [57]. The ability of probiotics to modulate apoptotic and anti-apoptotic proteins has also been illustrated in acetaminophen-induced hepatotoxicity [58] and chemotherapy-induced small and large intestinal apoptosis in rats [59].…”
Section: Mechanisms Of Probiotic Actionmentioning
confidence: 99%
“…Similar results were obtained by Wang et al who reported that the probiotic mixture, kefir, reduced ovalbumin induced apoptosis in mouse heart tissues by limiting levels of the pro-apoptotic proteins Bax and Bad, cytochrome c and caspase-3 [56]. Administration of probiotic mixtures also depressed expression of apoptosis linked proteins such as pro-apoptotic Bax, caspase-3 and -8, and anti-apoptotic Bcl-2 in the livers of rats fed a methionine choline-deficient diet [57]. The ability of probiotics to modulate apoptotic and anti-apoptotic proteins has also been illustrated in acetaminophen-induced hepatotoxicity [58] and chemotherapy-induced small and large intestinal apoptosis in rats [59].…”
Section: Mechanisms Of Probiotic Actionmentioning
confidence: 99%
“…Karahan et al . (2012) showed that MCDD-induced NASH in rats improved after treatment with probiotic mixture containing 6 or 13 bacterial strains that were isolated from the healthy human stool samples, likely in part through modulation of TNF-α activity [65]. Dextran sulphate sodium (DSS) treatment of Apolipoprotein E-deficiency mice caused liver histopathological features of steatohepatitis, which were prevented by VSL#3 treatment, through modulation of the expression of nuclear receptors, peroxisome proliferator-activated receptor-γ, Farnesoid-X-receptors, and vitamin D receptor [66].…”
Section: Nutritional Interventionsmentioning
confidence: 99%
“…Kim DH et al found that consumption of kefir (a probiotic beverage containing over 50 species of lactic acid bacteria and yeast) prevented obesity and NAFLD formation by restoring gut microbiota and enhancing fatty acid oxidation in HFD-fed mice [98]. Further evidence of beneficial effects on NAFLD prevention has been acquired in many studies by administering probiotics of mixed bacteria [99][100][101]. In addition to the direct impacts on the composition of gut microbiota, the beneficial effects of probiotics on NAFLD are also associated with their metabolic activities [53].…”
Section: Gut Microbiota-targeted Therapies Of Nafldmentioning
confidence: 99%
“…High fat and sucrose diet (HFSD)-induced NAFLD in rats [170] Influencing protein expression and decreasing steatohepatitis MCD diet-induced NASH in rats [99] Reducing obesity-related biomarkers and modulating the microbial community…”
Section: Probiotic Mixturesmentioning
confidence: 99%